Competition Drives Group Formation and Reduces Within Nest Relatedness in a Facultatively Social Carpenter Bee - Vickruck, Jess L.; Richards, Miriam H. (Frontiers in Ecology and Evolution, 2021)
Animals respond to competition among kin for critical breeding resources in two ways: avoidance of direct fitness costs via dispersal of siblings to breed separately, and formation of kin-based societies in which subordinates offset direct fitness costs of breeding competition via altruism and increased indirect fitness. Here we provide the first evidence that kin competition can promote the evolution of societies based on non-kin cooperation. In the facultatively social eastern carpenter bee, nests are a critical breeding resource in perpetually short supply, leading to strong competition among females. Observations of individually marked and genotyped females in conditions of high and low resource competition demonstrate that competition leads to resource sharing and group nesting. However, in contrast to almost all known animal societies, females avoid nesting with relatives, and disperse from their natal nests to join social groups of nonrelatives. This is the first example of a structured animal society based on avoidance of kin competition, rather than on selection for kin cooperation. By forming social groups of non-kin, females avoid the indirect fitness costs of kin competition among sisters, yet increase their chances of successful reproduction, and thus direct fitness, when forming colonies of non-relatives.